Pseudoaneurysm with Median Nerve Injury Caused by Right Radial Artery Puncture: A Case Report - Yachao Li; Zengming Xue; He Ma; Wei Zhang; Shaoping Nie; Changsheng Ma (Cardiovascular Innovations and Applications, 2021)
Background: Pseudoaneurysm with median nerve injury is a serious complication of radial artery puncture. It is very important to summarize the prevention and treatment experience of this complication through case discussion. Case report: A 66-year-old woman was admitted to the hospital because of “paroxysmal chest tightness and suffocation for 5 days.” Coronary angiography was performed. During insertion of the arterial sheath, the patient experienced severe pain in the right forearm, which radiated to the palm. The puncture sheath did not return blood after the sheath core was withdrawn. The sheath was removed and local compression was used to stop bleeding. There was no obvious bleeding at the puncture point, and the compression was removed 6 hours after the procedure. Local swelling and increased tension were seen in the right forearm. At the 1-week follow-up she exhibited swelling, high local tension, small blisters, and bluish-purple skin of the right forearm, with an acceptable right radial artery pulsation. She had severe pain in the affected limb, which radiated to the thumb, index finger, and middle finger. Case discussion: We discuss the causes of and treatment measures for pseudoaneurysm with median nerve injury caused by radial artery puncture.